Relationship of Age and Parity with Bone Mineral Density among Postmenopausal Women- A Study at Dhaka Medical College Hospital - Ghani, Tabassum; Kasem, Setara Binte; Paul, Ratna; Dhar, Jayanti Rani; Begum, Anwara (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Low Bone Mineral Density (BMD) leads to osteoporosis and increased bone fracture risk of a menopausal woman. Low Bone Mineral Density (BMD) is a major risk factor for osteoporosis and fragility fractures. Bone loss is accelerated following cessation of ovarian function and menstruation. Menopause is accompanied by estrogen deficiency and associated with bone loss. Generally accepted risk factors for osteoporosis in women are low BMI, age and duration of menopause. The effect of parity is controversial. So the aim of this cross-sectional observational study was to assess effect of parity on BMD. For this purpose total 100 women aged 50-70 years with parity three or more who had natural menopause were studied over the period of one year. All these women underwent measurement of Bone Mineral Density (BMD) at Dhaka Medical College Hospital (DMCH). Among 100 women 64 were para three to five, 30 were para 6-8 and only six were 9-11 para. BMD of L1-4 and total femur measured among para 3-5 women were (.938±.172,.855±.161) and it was (.851±.170,.769±.155) with para six to eight and (.765±.169, .656±.258) with para 9-11 respectively. ANOVA was done within and between groups, F = 3.996/4.959 ( P = .021/ .009). Negative correlation was found between parity and BMD of L1-4 and total Femur. This negative correlation was statistically significant. It can be concluded that with increasing parity BMD decreases. Bangladesh J Obstet Gynaecol, 2020; Vol. 35(1): 15-19